Stages of Dietary Behavior Change and Diet-Related Psychosocial Factors Related to Intake of Fat, Fruit and Vegetables Among Employees of Universiti Putra Malaysia - Wong, Chee Yen (2011)
A cross-sectional study of 348 adult employees (19 – 59 years old) of a public university was conducted to determine the relationship between stages of dietary behavior change and diet-related psychosocial scores with the intake of fat, fruit and vegetables. Information on demographic and socioeconomic characteristics, diet-related psychosocial factors and staging algorithm were obtained using a pre-tested self-administered questionnaire. Weight, height and waist circumferences were also measured. Dietary intake was assessed using two days 24-hours diet recall. Most respondents in this study were women (61%), Malay (93%), aged 20 – 49 years (92%), and had at least upper secondary education (99%). The average energy intake for men (1,702 kcal/day) and women (1,452 kcal/day) did not meet the recommended level. About 56% consumed > 30% of energy from fat. Most respondents (97%) consumed < 5 servings of fruit and vegetables. About 45% and 38% respondents were overweight/ obese and had at risk waist circumference, respectively Approximately 79% and 51% of respondents were in the preparation stage of fat reduction and increase in fruit and vegetable intake, respectively. Respondents perceived that “Decreased fat intake can prevent diseases” (4.54 ± 0.67) and “Fruit and vegetables are good for health” (4.51 ± 0.68) as important benefits to reduce fat and increase fruit and vegetable intake. “Cafeteria at worksite provides many foods high in fat” (3.24 ± 1.30) and “Presence of chemicals on the fruit and vegetables” (2.94 ± 1.17) were perceived as the main barriers to reduce fat and increase fruit and vegetable intake. Respondents had the highest confidence to choose and buy foods that are low in fats (3.59 ± 0.98) and to increase their fruit and vegetable intake even though a longer time is required for preparation (3.79 ± 1.00). Older (p < 0.01), married (p < 0.05) and respondents with higher monthly (p < 0.01) and household income (p < 0.01) also had higher intake of fruit and vegetables. More men than women were in the pre-contemplation/contemplation stage of fat reduction (p < 0.05) and increased fruit and vegetable intake (p < 0.05). Men also had lower perceived benefits (pfat < 0.001; pfv < 0.05) and higher perceived barriers (pfv < 0.01) than women to reduce fat and increase fruit and vegetable intake. Respondents who were overweight/obese and had at risk waist circumference had low energy intake (pbmi < 0.05; pwc < 0.01). They were also more likely to be in the preparation stage for fat reduction (pbmi < 0.001; pwc < 0.01) and had high perceived benefits of fat reduction (pbmi < 0.001; pwc < 0.05). Respondents aged > 30 years (p < 0.05), and with tertiary education (p < 0.01), higher monthly income (p < 0.05) and household income (p < 0.01) had significantly higher perceived benefits to increase fruit and vegetable intake than other respondents. Those with higher monthly income (p < 0.05) also had lower perceived barriers. Data showed that respondents in action/maintenance stages had higher perceived benefits (pfat < 0.001; pfv < 0.05) and self-efficacy (pfat < 0.001; pfv < 0.001), and lower barriers (pfat < 0.001; pfv < 0.05) to reduce fat and increase fruit and vegetable intake than those in the other stages. While respondents in the action/maintenance stages had higher adjusted mean serving intake of fruit and vegetables than those in other stages (p < 0.05), no significant group difference was found for energy, fat and percentage of fat energy intake. As majority of the respondents were in the preparation stages of dietary behavior change, cognitive strategies such as providing nutrition knowledge, and providing ways to overcome barriers and increase confidence to adopt healthy diet habits should be introduced to the respondents, especially men, and those who are younger, have lower education level, lower income, overweight and obese.